Rights of a wife in the case of conversion to Islam under the family law in Malaysia - Abdul Hak, Nora (Brill, 2012)
This article focuses on the issues of conversion of one of the party to a non-Muslim marriage to Islam. In Malaysia, there are some legal problems that need to be addressed particularly concerning the rights of a wife to the ancillary claims after the dissolution of the marriage such as maintenance, matrimonial property and custody. These issues have been discussed by the Malaysian courts in their judgments when they preside over cases involving conversion to Islam. Among the issues that have been raised is whether a non-Muslim wife is entitled to maintenance when her husband converted to Islam and if she is still entitled the next question is for how long. Other problem is which party that shall be entitled to the custody of the child and also issue concerning the legal status of the marriage. All these need to be discussed further as to whether there is a necessity to amend the existing relevant law. The article analyses the legal provisions and the cases that have been decided by the Malaysian courts on the conversion to Islam.